Report on the Special Miniworkshop "nano&Management". Issue 12 (25th November 2013) - Roth, Siegmar; Schmid, Michael; Skákalová, Viera; Duesberg, Georg S.; Kolaric, Ivica; Carroll, David; Maeda, Yoshihito; Suzuki, Motofumi
Abstract This is a short report on a special workshop on matters "around" science, held during the Kirchberg Winterschool 2013 on Electronic Properties of Novel Materials. The topics discussed are patents, experiences of small start‐up companies, funding and patenting strategies of large research institutes (like CRANN in Ireland and Fraunhofer Society in Germany) and success stories of cooperation between American university institutes and industrial partners (from invention over demonstrator, prototype, and pilot plant to production lines). (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)